"You Just Forge Ahead": The Continuing Challenges of Disaster Preparedness and Response in Long-Term Care. Issue 4 (18th September 2021) - Peterson, Lindsay J; Dobbs, Debra; June, Joseph; Dosa, David M; Hyer, Kathryn
Abstract: Background and Objectives: Protecting nursing home and assisted living community residents during disasters continues to be a challenge. The present study explores the experiences of long-term care facilities in Florida that were exposed to Hurricane Irma in 2017. Research Design and Methods: We used an abductive approach, combining induction and deduction. Interviews and focus groups beginning in May 2018 were conducted by telephone and in person with 89 administrative staff members representing 100 facilities (30 nursing homes and 70 assisted living communities). Analyses identified themes and subthemes. Findings were further analyzed using the social ecological model to better understand the preparedness and response of nursing homes and assisted living communities to Hurricane Irma. Results: 3 main themes were identified including: (1) importance of collaborative relationships in anticipating needs and planning to shelter in place or evacuate; (2) efforts required to maintain safety and stability during an unprecedented event; and (3) effects, repercussions, and recommendations for change following the disaster. Discussion and Implications: Preparing for and managing disasters in nursing homes and assisted living communities involves actions within multiple environments beyond the residents and facilities where they live. Among these, community-level relationships are critical.